Evolution of Digital Video Consumption Patterns - Martin Kuchta,; Andrej Miklošík, (Communication Today, 2025)
In today’s markets, companies have greatly shifted their focus towards customers as the entities creating the demand for companies’ products and sources of the revenues. The consumers shape and influence the current market trends with their desires and preferences; this requires reassessing and reshaping the offers and communications from companies. Most successful offer adjustments are built on relevant research and formed by consumer insights, often based on patterns of content consumption. The main aim of this article is to identify digital video marketing trends by combining two essential pillars: the data management possibilities related to the digital environment and the evolution of media consumption habits of consumers. The authors examine secondary data which is precisely selected, collected and shaped according to the research design requirements from available Consumer Barometer Research provided and processed by Google. Identification of the six most significant digital video trends to shape digital marketing in the following years can be considered the core of the authors’ research. The results are centred on innovation progress and consumers’ consumption habits and aim to outline possible approaches to digital video production and delivery to target groups for several future years.